T3 Acute Muscle Loss in the Critically Ill: From Bedside to Bench. (19th November 2012) - Puthucheary, ZA; Rawal, J; Mcphail, M; Connolly, B; Ratnayake, G; Sidhu, PS; Seymour, J; Chan, P; Hopkins, P; Shrikrishna, D; Hopkinson, N; Polkey, MI; et al.
Abstract : Background: Critical illness survivors demonstrate skeletal muscle wasting with associated functional impairment. We prospectively characterised this process, and defined the pathogenic roles of altered protein synthesis and degradation. Methods: Critically ill patients (n=63, 59% male, age 54.7±18.0 years, APACHE II score 23.5±6.5) were recruited <24 hours following Intensive Care Unit (ICU) admission. Muscle loss trajectory was determined through serial ultrasound measurement of rectus femoris cross-sectional area (RFCSA) and, in a subset (n=28), quantification of myofibre area (FibreCSA) and protein/DNA ratio in vastus lateralis biopsies. Histopathological analysis was also performed. Muscle protein synthesis and breakdown rates were determined ([1, 2–13C2]Leucine incorporation and D5-Phenylalanine dilution, n=11), and respective signalling pathways examined (Luminex technology and Western Blotting, n=33). Results: (i) RF CSA decreased significantly, (–17.7±12.1% [p<0.001]), but underestimated muscle loss determined by either FibreCSA (–10.3±10.9% vs.–17.5±30.2%, p=0.31), or assessment of protein/DNA ratio (–10.3±10.9% vs. –29.5±41.5%, p=0.03). (ii) Fall in RF CSA was greater in multi- than single-organ failure (–21.5±10.5% vs –7.2±9.7% respectively, p<0.0001), even by day 3 (–8.7±16.3% vs –1.8±9.6%, p<0.01). Those suffering ≥ 4 organ were worst affected (–26.3±12.0% vs –19.5±9.4% for 2–3 organ failure, p<0.01). (iii) Histopathological myofibre necrosis occurred in >50% (17/33) of subjects. (iv) Protein synthesis was depressed, to levels observed in fasted controls (0.035±0.018%/hr vs. 0.039±0.011%/hr respectively, p= 0.57). Synthesis rates increased by day 7 (0.076±0.066%/hr, p=0.07) to levels associated with healthy fed controls (0.065+0.018%/hr, p0.30). These effects were independent of nutritional calorie and protein load received. (v) Protein breakdown remained elevated throughout (8.5±5.7 to 10.6±5.7 mmol phe/min/IBW, p=0.4). (vi) Principal component analysis of patterns of intracellular signalling suggested an orchestrated programme of increased breakdown (r –0.83, p0.005) and depressed synthesis (r–0.69, p0.041). Conclusions: Skeletal muscle wasting (defined for the first time by three independent measures) (1) occurs early and rapidly in critical illness and (2) is greatest in those with multi-organ failure. Suppression of protein synthesis and increases in catabolism (isotope uptake and intracellular signalling data) were shown, for the first time, to underpin these changes. Importantly, these overall effects appear independent of feeding status, and also to be commonly associated with (previously unrecognised) myonecrosis. ZAP is a National Institute of Health Research Research Fellow, and has received funding from the European Society of Intensive Care Medicine, Guys and St Thomas Comprehensive Biomedical Research Centre and the Whittington Hospital NHS Trust.